Assessment of geotechnical properties of British coal measures rocks for construction. - Nahazanan, Haslinda; Asadi, Afshin; Clarke, Sam
In opencast coal mines, a series of sandstones, shales and coal usually accompany a coal seam that formed coal measures. Due to rapid development in UK, opencast coal mines are reinstated with substantial depths of fill materials to provide land for the development. Therefore, it is crucial to understand the durability and compression characteristics for most engineering projects involving this material. Laboratory experiments such as slaking immersion test, slaking index test, oedometer test and Rowe cell consolidation test were carried out on samples taken from three different sites in UK to simulate changes of moisture content of the material. Collapse compressions upon introduction of water were exhibited by all three types of coal measures rocks up to 15% to 30%. The large strains are believed to be due to the wetting of the outer part of the particles acting as a lubricant, causing the wetted particles to slide past one another allowing the soil to collapse. It is concluded that the susceptibility of each coal measures rocks to rapid deterioration in the presence of water are diverse dependent upon its proportion of clay and silt size.